Confinement of PMo12 in hollow SiO2-PMo12@rGO nanospheres for high-performance lithium storage. Issue 2 (16th November 2020) - Hu, Hanbin; Jia, Xueying; Wang, Jiaxin; Chen, Wei; He, Lei; Song, Yu-Fei
Abstract : High-performance lithium storage was achieved by the confinement of PMo12 in hollow SiO2-PMo12@rGO nanocomposites. Abstract : To meet the ever-increasing demand for energy storage in social development, high energy density battery materials are required. Herein, we successfully designed a novel hollow SiO2 -PMo12 @rGO nanosphere via electrostatic interaction (PMo12 is H3 PMo12 O40 ; rGO is reduced graphene oxide). The PMo12 clusters were electrostatically attached onto the surface of the hollow SiO2 spheres with amino terminals, and the rGO layer was further externally wrapped on the composites to confine the POM clusters. The hollow SiO2 -PMo12 @rGO nanocomposite was used as an anode material for lithium-ion batteries (LIBs). It showed an overall reversible capacity of 720 mA h g −1 for 100 cycles at a current density of 100 mA g −1, which was twice as large as that of the hollow SiO2 @rGO and SiO2 -PMo12 composites. The hollow structure of the composites provided abundant void space to buffer the volume changes during the lithiation and delithiation processes. Confinement of PMo12 with the rGO layer prevented the POM clusters from dissolution in the electrolyte, improved the migration of Li + and enhanced the conductivity of the entire material. The superior performance of the hollow SiO2 -PMo12 @rGO nanosphere mainly resulted from the synergistic effects from the three components.